Comparative Analysis of Traditional Mining with Big Data Mining - Dr. Sushil Kumar Sharma; Dr. Naveen Verma (Innovative Research Thoughts, 2023)
In this research paper, Big data storage, traditional data mining, Big data mining, Social recommendation, Scalable social recommendation and social recommendation improvement using deep learning are analyzed with key stress on comparaing Traditional Mining with Big Data Mining. The issues such as scalability, sparsity, cold start, data variety etc. are addressed by proposed approaches.